The shaded side of the UHC cube: A systematic review of human resources for health management and administration in social health protection schemes - Konrad Obermann; Tata Chanturidze; Bernd Glazinski; Karin Dobberschuetz; Heiko Steinhauer; Jean-Olivier Schmidt (Health Economics Review, 2018)
Managers and administrators in charge of social protection and health financing, service purchasing and provision play a crucial role in harnessing the potential advantage of prudent organization, management and purchasing of health services, thereby supporting the attainment of Universal Health Coverage. However, very little is known about the needed quantity and quality of such staff, in particular when it comes to those institutions managing mandatory health insurance schemes and purchasing services. As many health care systems in low- and middle-income countries move towards independent institutions (both purchasers and providers) there is a clear need to have good data on staff and administrative cost in different social health protection schemes as a basis for investing in the development of a cadre of health managers and administrators for such schemes. We report on a systematic literature review of human resources in health management and administration in social protection schemes and suggest some aspects in moving research, practical applications and the policy debate forward.
Keywords: I11; I13; J24; J45; 330; Human resources; Health financing; Health administration; Health care purchasing; Management; UHC